GLUE ABUSE IN LOME: INVESTIGATION AND TOXICOLOGICAL STUDY ON WISTAR RATS - Pierre, Badjabaissi; Diallo, Aboudoulatif; Povi, Lawson Evi; Amegbor, Koffi; Gadegbeku, Kwashie Eklu; Moesch, Christian; Creppy, Edmond; Gbeassor, Messanvi (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objectives: Volatile substances abuse (VSA) is considered as one of the most dangerous forms of drug abuse leading to serious accidents and fatalities. This study aims to assess the extent and dangers of the sniffing of '' Dia'' glue, used by the vulcanizer to paste the cars' tires. Methods: The first phase of the study involved a survey with vulcanizers of the district I of Lome. The effect of the glue was then evaluated on female wistar rats, by inhalation' in a 1L capacity jar for a period of 5 min at doses of 320 mg/l and 640 mg/l. The rat behavioral changes, driving test, tail flick test, tolerance test and 28 d subchronic toxicity test were carried out. Results: The survey has identified street vendors as glue sniffers (80.95%). The most cited reason for the glue inhalation was the tailism (79.76%) and the presumed effect was to feel stronger (76.19%). On wistar rat, â€˜â€˜Dia'' glue has induced some behavioral changes. It has increased significantly the righting recovery reflex time and the maintaining time of the tail in warm water. After 28 d exposition, 5 min per day, â€˜â€˜Dia'' glue increased significantly (pË‚0.001) the relative weight of the spleen, the AST (pË‚0.001) and ALT (pË‚0.001). It has also induced an anaemia associated with a thrombocytosis. The analysis of the glue by GC-HS-MS has showed a high amount of toluene (65%), a lesser proportion of dimethyl cyclohexane, ethyl acetate and traces of benzene, ethylbenzene and xylene. Conclusion: The sniffing of â€˜â€˜Dia'' glue is very dangerous. Addiction especially that which is done with volatile substances must, therefore, be carefully controlled. Â